The role of calpain in spinal cord degeneration in experimental Pаrkinson’s disease - V. H. Knaryan (ՀՀ ԳԱԱ հրատ.)
In this review the critical role of Са2+-dependent protease calpain in the cascade of intracellular processes, leading to degeneration and death of spinal cord neurons in experimental models of Parkinson’s disease (PD) is discussed. In experimental conditions parkinsonian neurotoxins 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) and rotenone cause the activation of calpain and caspase-3, which subsequently cleave cytoskeletal protein spectrin and axonal neurofilament light protein (NF-L). Ակնարկում քննարկվում է Ca2+-կախյալ պրոտեազի` կալպաինի առանցքային դերը ներբջջային պրոցեսների կասկադում, որոնք կործանարար են ազդում ողնուղեղի նեյրոնների վրա փորձարարական Պարկինսոնի հիվանդության (ՊՀ) ժամանակ: Պարկինսոնիզմ առաջացնող նեյրոտոքսինների՝ 1-մեթիլ-4-ֆենիլ-1,2,3,6-տետրահիդրո-պիրիդինի (ՄՖՏՊ) և րոտենոնի ազդեցության արդյունքում ակտիվանում են կալպաինը և կասպազ-3-ը, որոնք քայքայում են բջջի կառուցվածքային սպիտակուցը՝ սպեկտրինը և աքսոնների նեյրոֆիլամենտի թեթև սպիտակուցը: В обзоре обсуждается ключевая роль Са2+-зависимой протеазы кальпаина в каскаде внутриклеточных процессов, ведущих к вырождению нейронов спинного мозга при болезни Паркинсона (БП). В экспериментальных условиях нейротоксины 1-метил-4-фенил-1,2,3,6-тетрагидропиридин (МФТП) и ротенон, вызывающие паркинсонический синдром, запускают активацию кальпаина и каспазы-3, которые расщепляют структурный белок цитоскелета спектрин и аксональный белок нейрофиламента легкого (NF-L).
Keywords: Biology; Biochemistry; Medicine